2022
DOI: 10.1021/acsaem.1c03803
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Interfacial Evolution in Extremely Fast Charged Lithium-Ion Batteries

Abstract: Interfacial reaction mechanisms at the anode/separator interface play a central role in the performance and safety of lithium-ion batteries during fast charging. We report a mechanistic study on the evolution and interactions of the aging mechanisms at the anode/separator interface in lithium cobalt oxide/graphite pouch cells charged with variable charging rates (1–6C) over 10 cycles. In situ electrochemical measurements, including voltage relaxation, Coulombic efficiency, and direct current internal resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Initially, the graphite half-cell was discharged at a high current in the LiDFBOP-added electrolyte to produce an initial SEI layer with numerous cracks. 38 Then, the cell was charged at a low current to allow the oxidation products of the electrolyte to completely fill the fractures in the initial SEI.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the graphite half-cell was discharged at a high current in the LiDFBOP-added electrolyte to produce an initial SEI layer with numerous cracks. 38 Then, the cell was charged at a low current to allow the oxidation products of the electrolyte to completely fill the fractures in the initial SEI.…”
Section: Resultsmentioning
confidence: 99%
“…At a lower charging rate, 30 the dendrites were formed at a lower rate and thus had more time to react with the electrolyte, leading to a thicker passivation layer during the plating process. 43 …”
Section: Resultsmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins At a lower charging rate, 30 the dendrites were formed at a slower rate and thus had more time to react with the electrolyte, leading to a thicker passivation layer during the plating process. 43 Spatiotemporal mapping was performed to study the formation of nanoscopic i-Zn (Figure 3c). The results indicated that the discharging rate plays an important role.…”
Section: Effects Of Charging/discharging Current Densitymentioning
confidence: 99%
“…[9] Li plating is associated with the processes including the Li + diffusion in the anodes and cathodes, Li + transport in the bulk electrolyte, Li + de-solvation before entering the solid electrolyte interphase (SEI), and the transport of bare Li + through SEI. [10] Therefore, Li + transport in the electrolyte and electrode/electrolyte interphase (EEI) is a crucial factor influencing the fastcharging performance of LIBs. The conventional electrolyte has poor redox stability, which continuously decomposes and causes the formation of thick EEI layers during fast-charging, leading to slow Li + transport kinetics through the EEI.…”
Section: Introductionmentioning
confidence: 99%
“…Li plating is associated with the processes including the Li + diffusion in the anodes and cathodes, Li + transport in the bulk electrolyte, Li + de‐solvation before entering the solid electrolyte interphase (SEI), and the transport of bare Li + through SEI [10] . Therefore, Li + transport in the electrolyte and electrode/electrolyte interphase (EEI) is a crucial factor influencing the fast‐charging performance of LIBs.…”
Section: Introductionmentioning
confidence: 99%